BCH codes in UFMC: A new contender candidate for 5G communication systems - Ghasan Ali Hussain; Lukman Audah (Institute of Advanced Engineering and Science, 2021)
Nowadays, fifth generation (5G) wireless network is considered one of the most important research topics in wireless industry and it will be substituting with fourth generation (4G) in several aspects. Although the robustness of orthogonal frequency division multiplexing (OFDM) system against channel delays which is the reason behind using it in LTE/LTE Advanced however, it is suffering from high peak to average power ration (PAPR) and out of band side lobes. So, universal filtered multi-carrier (UFMC) technique is considered a new modulation scheme for 5G wireless communication system to overcome on the common OFDM demits. In contrast, to achieve reliable data transmission in digital communication systems, using error correcting codes are considered an essential over noisy channels. In this paper, BCH code has been used for UFMC system over AWGN. The results showed that using BCH codes in UFMC contributed in enhancing BER performance while could decreasing both of PAPR and OOBE values better than conventional OFDM system.